ASPEK HUKUM DALAM AUDIT KOPRASI - Semaun, Syahriyah (DIKTUM: Jurnal Syariah dan Hukum, 2010)
Cooperation can proroses Audit service to public accountan which going to do increasing efficiency, management who has open carrateristic and protect the side who has on interest and some reports which cooperation needed appropriate. This inspection be done reach âGood Corporate Governanceâ which pinpose to create good value for all ones who have an interest therefore, cooperation management and stake out must be understand all about cooperation accountan which are appropriate on standard for general occur, where as for internal auditing in cooperation must be really understand auditing standard which is valid for general and should be have independent spirit.